2015
DOI: 10.5811/westjem.2015.8.27908
|View full text |Cite
|
Sign up to set email alerts
|

Association of Emergency Department Length of Stay and Crowding for Patients with ST-Elevation Myocardial Infarction

Abstract: IntroductionWith the majority of U.S. hospitals not having primary percutaneous coronary intervention (pPCI) capabilities, the time spent at transferring emergency departments (EDs) is predictive of clinical outcomes for patients with ST-elevation myocardial infarction (STEMI). Compounding the challenges of delivering timely emergency care are the known delays caused by ED crowding. However, the association of ED crowding with timeliness for patients with STEMI is unknown. We sought to examine the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The discharging of patients especially with high-risk clinical characteristics [51] and misleading the patients to other departments [18] have adversely impacted the patients’ health consequences. These situations could increase the time of accepting and transferring the outpatients [79] and increase patient’s admission and re-admission rates [42, 61, 64, 89] consequently a reduced discharging rate of patients [51]. The increased hospitalization of patients caused overuse of all facilities [64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharging of patients especially with high-risk clinical characteristics [51] and misleading the patients to other departments [18] have adversely impacted the patients’ health consequences. These situations could increase the time of accepting and transferring the outpatients [79] and increase patient’s admission and re-admission rates [42, 61, 64, 89] consequently a reduced discharging rate of patients [51]. The increased hospitalization of patients caused overuse of all facilities [64].…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that ED overcrowding negatively effects on patients’ health, healthcare delivery services and the communities [4249, 52–61, 64, 79, 89]. The high workload caused prolonged healthcare services and clinical decision making and raised patients’ LOS [53, 54, 56, 60, 61, 63–78].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that the timeliness of care in time-sensitive conditions, such as myocardial infarction, is less sensitive to the adverse effects of crowding. [ 7 , 8 ] This has been explained by the use of standardized protocols to rapidly diagnose and treat these patients in the ED. [ 7 ] In our study, chest pain or arrhythmia was associated with a relatively small increase of LOS in both high- and low-acuity patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both 6,23,24,38,40,42,44,46,47,49,52 Pain: abdominal pain, 19 back Pain, 24 CVA, Stroke 6,43,44 Intubated Trauma patients 45 Sepsis 8,53 Hip Fracture 12 All Patients 5,9,38,40,42,[47][48][49]51 Adults 6,7,12,19,[22][23][24]38,[43][44][45][46]52,53 All patients 8,9,40,42,[47][48][49][50][51] < or > 8 hours 43 Quartiles 6,8,19,22-24,48,52 Both …”
Section: Dovepressmentioning
confidence: 99%